Real-Time Guitar Preamp Simulation Using Modified Blockwise Method and Approximations. (22nd February 2011) - Macak Macak, Jaromir Jaromir; Schimmel Schimmel, Jiri Jiri
Abstract : The designing of algorithms for real-time digital simulation of analog effects and amplifiers brings two contradictory requirements: accuracy versus computational efficiency. In this paper, the simulation of a typical guitar tube preamp using an approximation of the solution of differential equations is discussed with regard to accuracy and computational complexity. The solution of circuit equations is precomputed and stored in N-D tables. The stored values are approximated, and therefore different approximation techniques are investigated as well. The approximated functions are used for output signal computation and also for circuit state update. The designed algorithm is compared to the numerical solution of the given preamp and also to the real preamp.